Measuring progress with clinical governance development in New Zealand: perceptions of senior doctors in 2010 and 2012 - Gauld, Robin (BMC Health Serv Res, 2014)
BACKGROUND: Clinical governance has become a core component of health policy and services management in many countries in recent years. Yet tools for measuring its development are limited. We therefore created the Clinical Governance Development Index (CGDI), aimed to measure implementation of expressed government policy in New Zealand. METHODS: We developed a survey which was distributed in 2010 and again in 2012 to senior doctors employed in public hospitals. Responses to six survey items were weighted and combined to form the CGDI. Final scores for each of New Zealand’s District Health Boards (DHBs) were calculated to compare performances between them as well as over time between the two surveys. RESULTS: New Zealand’s overall performance in developing clinical governance improved between the two studies from 46% in 2010 to 54% in 2012 with marked differences by DHB. Statistically significant shifts in performance were evident on all but one CGDI item. CONCLUSIONS: The CGDI is a simple yet effective method which probes aspects of organisational commitment to clinical governance, respondent participation in organisational design, quality improvement, and teamwork. It could be adapted for use in other health systems.